THE PREFACIAL DISCOURSE OF THE BILINGUAL FRENCH-ROMANIAN/ROMANIAN-FRENCH 19TH CENTURY DICTIONARIES - GENCĂRĂU, Oana Aurelia; GENCĂRĂU, Ștefan (Studia Universitatis Babeș-Bolyai Philologia, 2019)
The Prefacial Discourse of the bilingual French-Romanian/ Romanian-French 19th Century Dictionaries. We systematically return to our 19th century bilingual lexicography, and this time we turn towards textual sequences preceding the respective lexicographic body; these are interesting for those seeking to understand how the practice of dictionary compilation has evolved; these textual sequences, be they the preface or the inscription, show the way the configuration discourse of a lexicographical work comes, little by little, to confirm the presence of the model, to claim the method and to subordinate the undertaking of the interest of one or several categories of addressees. Rezumat. Discursul prefațial al dicționarelor bilingve francezo-române/ româno-franceze din secolul al XIX-lea. Revenim sistematic la lexicografia noastră bilingvă din secolul al XIX-lea și ne îndreptăm de data aceasta spre secvențe textuale ce precedă corpul lexicografic respectiv ; acestea prezintă interes pentru cel ce dorește să înțeleagă cum au evoluat practicile de alcătuire a dicționarelor; aceste secvențe textuale, fie că e vorba de prefață, fie că e vorba de dedicații, arată cum discursul de configurare a unei opere lexicografice ajunge, încetul cu încetul, să confirme prezența modelului, să reclame metoda și să-și subordoneze întreprinderea interesului unui sau unor categorii de destinatari. Cuvinte cheie: vocabular, dicționar bilingv, prefață, dedicație, lexicografie bilingvă.